Enhanced biogas production from anaerobic co-digestion of pig slurry and horse manure with mechanical pre-treatment. Issue 10 (29th April 2019) - Lopes, Madalena; Baptista, Patrícia; Duarte, Elizabeth; Moreira, António L. N.
ABSTRACT: Enhanced biogas production from anaerobic co-digestion of pig slurry and horse manure with mechanical pre-treatment. In this study, co-digestion of horse manure and pig slurry was investigated in a continuously stirred tank reactor, with a mechanical pre-treatment. Experiments were conducted at 37°C, with hydraulic retention times of 23 days and increasing shares of horse manure, corresponding to different horse manure to pig slurry ratios (HM:PS) equal to 0:100, 10:90, 13:87 and 20:80, in terms of percentage of inlet volatile solids (%VS inlet). The results show that the best synergetic effect between the microbial consortia of pig slurry and the high Carbon to Nitrogen ratio (C/N) of horse manure is obtained for the mixture of 20:80%VS inlet, yielding the highest specific methane production (SMP = 142.6 L kgTCOD −1 ) and the highest soluble chemical oxygen demand (SCOD) reduction (68.5%), due to the high volatile dissolved solids content and soluble chemical oxygen demand to total chemical oxygen demand ratio (SCOD/TCOD). Thus, co-digestion of horse manure and pig slurry is shown to be a promising approach for biogas production and as a waste treatment solution. Furthermore, the analysis provides a methodology for the pre-treatment of these substrates and to investigate into the best combination for improved biogas production.